Monitoring anaerobic performance in combat sport athletes - call for test specificity - Batra, A. (Sport Performance & Science Reports, 2019)
Aim.The aim of this study was to investigate the relationships between changes in anaerobic performance examined by WAnT and changes in 30 second kicking performance in combat sport athletes. We hypothesized that changes in WAnT do not re ect the changes in sport-speci c performance despite taxing the same energy systems.